Pengaruh Pemberian Minuman Kunyit Asam terhadap Perubahan Skala Nyeri pada Siswi Kelas XII SMK Kesehatan Fahd Islamic School dengan Disminore Primer Tahun 2023 - Dina Raidanti; Rina Wijayanti; Koswina Pinka; Ardelia Pratiwi; Wahidin Wahidin (Lembaga Pengembangan Kinerja Dosen, 2025)
Puberty in adolescents is marked by menstruation every month which lasts 5 to 7 days. Menstruation is a natural and natural event, although in reality many of them experience dysmenorrhoea problems ranging from mild to severe because each woman has a different level of pain. Psychologically, dysmenorrhoea will greatly interfere with physical activity even until adolescents do not enter during learning. Dysmenorhoe is a painful period with no cause of symptoms and is not associated with a gynecological disorder. Women with primary dysmenorrhea have higher levels of prostaglandins compared to women without dysmenorrhea. There are 10 students at SMK Kesehatan Fahd Islamic School, 7 of them have dysminorhea and until now the factors causing dysmenorrhea are unknown. In this PKM activity, health counseling is carried out as an effort to increase knowledge and behavior in overcoming pain during menstruation, namely by herbal methods. Turmeric which is processed as a drink is one of the efforts for teenagers to reduce pain during menstruation or known as dysminorea. The delivery media used are leaflets, power points, and videos. An evaluation will be carried out by providing a pre-test before the provision of counseling materials and post-tests after the provision of counseling materials. The results of the study showed that, in the measurement of the pre-pain scale, the results were obtained that the average pain was 1.75 with a median value of 2.00 with the most pain scale of 3 with the lowest pain of 0 and the highest 3. In the measurement of the post pain scale, the average result of after pain was 3.75 with a median value of 4.00 with the most pain scale of 4 with the lowest pain of 1 and the highest 5. The conclusion of the statistical test was that there was an effect of giving sour turmeric drink in the control group on changes in pain scale in female students with primary dysminore.